Tindak Tutur Komisif Pada Pedagang di Pasar Induk Cureh Kabupaten Bireuen (Kajian Pragmatik) - Herawati Herawati; Emilda Emilda; Masithah Mahsa (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This study aims to describe the functions and forms of commissive speech acts used by vendors at Induk Cureh Market, Bireuen Regency. This research employs a qualitative approach with a descriptive method. The data consist of excerpts from the speech between vendors and buyers that contain commissive speech acts. The data source for this research is the vendors at Induk Cureh Market, Bireuen Regency. Data collection techniques included observation, recording, and notetaking. Based on the findings, 43 instances of commissive speech acts were identified. The functions of these commissive speech acts are divided into three categories: (1) promising, found in 8 instances; (2) offering, found in 30 instances; and (3) vowing, with 5 instances.